Identification and Prioritization of Contextual Factors Influencing the Improvement of Continuous Training for Employees in Universities of Baghdad Province - Al Hiani, Farah Khairullah Fawwaz; Hosseinpour, Mohammad; Fakhri Saleh, Muneer; Saeidian Khorasghani , Narges (Assessment and Practice in Educational Sciences, 2026)
The present study aimed to identify and prioritize the contextual factors influencing the improvement of continuous training for employees in universities of Baghdad Province. The research was applied in terms of purpose and exploratory in terms of methodology. Grounded theory was employed to identify and prioritize the contextual factors affecting the enhancement of continuous training. Data were collected through semi-structured interviews with 15 selected academic experts using the snowball sampling method. Data analysis was conducted in three stages: open coding, axial coding, and selective coding. The findings revealed that contextual factors play a pivotal role in facilitating and enhancing the effectiveness of continuous training programs and were hierarchically classified according to their importance and influence. At the top of this hierarchy was managerial support and leadership, which, by fostering a motivational, supportive, and participatory atmosphere, plays a fundamental role in encouraging employees to actively engage in learning processes. The second-ranked factor was the university’s supportive infrastructure and resources; access to equipment, financial resources, and modern educational technologies significantly strengthens employees’ ability to benefit from training initiatives. The third most important factor was organizational culture and employees’ attitudes toward learning, which facilitates the acceptance of continuous learning and feedback, contributing to the creation of a dynamic and learning-oriented environment.